SUSTENTABILIDAD Y PRODUCCIÓN DE CONOCIMIENTO EN LA EDUCACIÓN UNIVERSITARIA (Agroindustria, Sociedad y Ambiente, 2021)
Development goals drive the adoption of measures that promote prosperity while protecting the planet. This implies another look at the production of knowledge; and to act on three axes: to promote the fight against inequalities, overcoming poverty and combating climate change. This represents for university education a demand for answers, both in the production of knowledge and technologies friendly to the environment, as possible solutions to the problems they represent. Transformative learning and the sustainability approach offer opportunities in this task to change the realities of the human being and its frames of reference for the necessary analysis. The present study aimed to review learning experiences of university students participating in activities contextualized with a transformative perspective; and is part of a wider research on university educational practice. From a qualitative perspective and based on a hermeneutical analysis, the work involved the selection and observation of three experiences, as well as the analysis of the reflections and conversations about the experience with the teachers. Among the results, highlights the greater understanding and commitment of the students and teachers with the solutions, a sustained motivation in the activity, as well as a displacement of the purposes with which they approach the rest of their university activities. In closing, approaches, transformative learning and sustainability allow a broad and systemic vision in the structuring of university educational experiences, and offer alternatives in the production of knowledge.
Keywords: Sustainability, knowledge, university education, transformative learning.